Immune Checkpoint Inhibitors Plus Single-Agent Chemotherapy for Advanced Non-Small-Cell Lung Cancer After Resistance to EGFR-TKI - Deng, Haiyi; Lin, Xinqing; Xie, Xiaohong; Yang, Yilin; Wang, Liqiang; Wu, Jianhui; Liu, Ming; Xie, Zhanhong; Qin, Yinyin; Zhou, Chengzhi (Frontiers in Oncology, 2021)
Purpose Platinum-based chemotherapy remains the classic treatment option for patients with advanced non-small-cell lung cancer (NSCLC) who progress while receiving treatment with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs). In this study, we analyzed real-world outcomes of treatment with immune checkpoint inhibitors (ICIs) combined with platinum-free chemotherapy in patients with NSCLC after developing resistance to EGFR-TKIs. Methods This retrospective study included patients with mutation-positive NSCLC after developing resistance to EGFR-TKIs. Patients who received chemotherapy alone plus ICIs with or without anti-angiogenic drugs (cohort A) or platinum-based chemotherapy (cohort B) between February 2019 and August 2020 were enrolled. Clinical characteristics, EGFR mutation status, response to therapy, and adverse events (AEs) were retrospectively analyzed. Results Seventeen patients were eligible and included in the analysis, including 8 in cohort A and 9 in cohort B. After a median follow-up of 7.6 months, the median progression-free survival was 6.5 months [95% confidence interval (CI), 6.1 to 7.0] in cohort A and 3.6 months (95% CI, 1.3–5.8) in cohort B (hazard ratios, 0.22; 95% CI, 0.05–0.93; P = 0.039). The overall response and disease control rates were 50% and 100% in cohort A, and 22% and 89% in cohort B, respectively. Adverse events of grade 3 or higher occurred in 25% of the patients in cohort A and in 33.3% of the patients in cohort B. Conclusion ICIs plus platinum-free, single-agent chemotherapy provides promising progression-free survival and overall response rate benefit, along with a low rate of severe AEs in patients with EGFR-TKI-resistant advanced NSCLC.